2000
DOI: 10.1034/j.1399-3003.2000.16a02.x
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorm-associated asthma in an inland town in south-eastern Australia. Who is at risk?

Abstract: The aim of the study was to characterize patients at risk of asthma exacerbation during spring thunderstorms and identify potential measures to ameliorate the impact of those events.A case-control study was conducted among patients aged 7±60 yrs, who attended Wagga Hospital (NSW, Australia) for asthma during the period of 1 June 1997 to 31 October 1997. One hundred and eighty-three patients who attended on 30 and 31 October 1997 were the cases and the remaining 121 patients were the controls. Questionnaire dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
4
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 33 publications
11
134
4
2
Order By: Relevance
“…Moreover, true asthma exacerbations may occur during dry days in some patients naturally exposed to pollens (1943,1944), probably because pollen allergens can be born by submicronic particles which can penetrate deeply into the airways (399). Thunderstorm-induced asthma is often, but not always, associated with pollen sensitization (401,404,(1945)(1946)(1947).…”
Section: Common Risk Factorsmentioning
confidence: 99%
“…Moreover, true asthma exacerbations may occur during dry days in some patients naturally exposed to pollens (1943,1944), probably because pollen allergens can be born by submicronic particles which can penetrate deeply into the airways (399). Thunderstorm-induced asthma is often, but not always, associated with pollen sensitization (401,404,(1945)(1946)(1947).…”
Section: Common Risk Factorsmentioning
confidence: 99%
“…Severe asthma exacerbations may occur in patients with newly diagnosed [21] or well-controlled [22] asthma or even by atopic patients with no previous asthma symptoms [23]. Exacerbations, by definition and in clinical practice, are identified by a change from and return to previous status, i.e.…”
Section: Is a Concept Of Asthma Severity Still Needed?mentioning
confidence: 99%
“…In Melbourne, two large asthma outbreaks (rapid increase in hospital or general practitioner visits for asthma) coincided with thunderstorms [14]. In Wagga Wagga, 215 asthmatic subjects attended the local emergency department, 41 of whom required admission to hospital [18]. In south eastern Australia, MARKS et al [19] observed that the incidence of excess hospital attendances for asthma during late spring and summer was strongly linked to the occurrence of thunderstorm outflows and demonstrated that the arrival of a thunderstorm outflow was accompanied by a large increase in the concentration of ruptured pollen grains in ambient air.…”
Section: Thunderstorms and Allergic Asthma Epidemics In Pollen Allergmentioning
confidence: 99%